Parents’ Struggles and Students’ Learning Motivation: A Search for Connection - Nasution, Liah Rosdiani (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2022)
This study is a non-experimental research that explores the relationship between parents’struggles and students’ learning motivation in higher education. Theories of Parental Involvement and The Expectancy Theory of Motivation are used as foundations of this research. 389 students are selected to participate in filling out surveys administered online to accommodate the transition to online learning recently. The correlational bivariate analysis results show that the relationship (p) between the two variables are significant at 0,01 level and that the strength of the relationship (r) is shown to be strong at 0,60 level. This means that the more struggles experienced by parents, the higher the students’ learning motivation become. Thus, the null hypothesis in this study is rejected. This study is supposed to be a preliminary investigation on the topic and further research is needed. Suggestions to the parties involved in the teaching practice are made.